Personalized approach to the treatment of rectal fistulas - S.E. Katorkin; G.V. Yarovenko; O.E. Lisin; A.V. Zhuravlev; E.V. Shestakov; A.V. Arustamyan (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2024)
Background. Rectal fistula is a common anorectal disease of a benign nature, which is a pathological canal between the perianal skin and the rectum. Treatment of rectal fistulas is only possible through surgery. The type of surgical intervention depends on the type of fistula, its topography relative to the fibers of the anal sphincters, length, as well as additional complicating factors such as the presence of scar tissue in the anal canal, branched fistulous tracts and purulent cavities. Materials and methods. In the scientific literature one can find many methods of surgical treatment of complex rectal fistulas, but the statistical results are disappointing - relapses of the disease reach 90%, and postoperative insufficiency of the anal sphincter - 50%. Results and conclusions. This article presents a clinical case of the successful use of a combination of new methods of surgical treatment of a pararectal fistula, and also reflects the dynamics of postoperative observation of the patient for 12 months. The demonstrated combined method of surgical treatment of a patient with a complex high transsphincteric pararectal fistula is sphincter-preserving, and the results of surgical treatment showed its effectiveness in terms of the development of disease relapse.